Eye-Related Emergency Department Visits and The Opioid Epidemic: a 10-Year Analysis. (3rd July 2020) - Usmani, Bushra; Latif, Asad; Amarasekera, Sohani; Mukhtar, Sabrina; Iftikhar, Mustafa; Kherani, Saleema; Sepah, Yasir J.; Raghavan, Deepta; Smith, William D.; Jhanji, Vishal; Dansingani, Kunal K.; Shah, Syed M. A.
ABSTRACT: Purpose: To describe the epidemiology of Emergency Department (ED) visits related to opioid abuse with primary ophthalmic diagnoses in the United States (US). Methods: This retrospective cross-sectional study used National ED Sample (NEDS) (2006–2015), a representative sample of all US EDs, to analyze and compare the epidemiology of primary ophthalmic diagnoses in opioid abusers and a control group of non-opioid users. National incidence and descriptive statistics were calculated for demographics and prevalent diagnoses. Multivariable logistic regression was used to compare outcomes between primary ophthalmic diagnoses in opioid and non-opioid abusers. Results: An estimated 10, 617 visits had a primary ophthalmic diagnosis and an accompanying opioid abuse diagnosis, and the incidence increased from 0.2 in 2006 to 0.6 per 100, 000 US population in 2015. Opioid abuse group had more adults (6, 747:63.5%) and middle-aged (3, 361:31.7%) patients, while in controls adults (7, 905, 003:40.4%) and children (4, 068, 534:20.8%) were affected more. Leading etiologies were similar: traumatic and infectious etiologies were most common; however, opioid abuse patients had more severe ophthalmic diagnoses such as orbital fractures (8.4%), orbital cellulitis (7.4%), globe injury (3.4%) and endophthalmitis (3.2%) compared to controls. Patients in the opioid abuse group were also more likely to be admitted (adjusted Odds Ratio [aOR], 28.38 [95% CI, 24.50–32.87]). Conclusions: In the era of opioid crisis, an increase in ED visits with ophthalmic complaints is seen, with increasing direct and indirect costs on the healthcare system. More research is needed to establish causality and devise strategies to lower this burden.